Estimating social returns to education using Singapore data. - Wu, Zhen. (2008)
Singapore experienced a long period of rapid GDP growth rates in the past decades. It led the “Asia’s miracle” and proved to be the most successful economy among the Asian “four tigers”. Due to scarcity of natural resources, Singapore’s human capital development was critical to achieve the goal of a “city of excellence and a society of distinction”. Literature on the relationship between earnings and education has been absent for decades.